Dansgaard-Oeschger and Heinrich event temperature anomalies in the North Atlantic set by sea ice, frontal position and thermocline structure - Pedro, J.B. (2022)
We use eighteen timescale-synchronised near-surface temperature reconstructions spanning 10-50 thousand years before present to clarify the regional expression of Dansgaard-Oeschger (D-O) and Heinrich (H) events in the North Atlantic. The North Atlantic Drift region shows D-O temperature variations of ca. 2-5?? with Greenland-like structure. The Western Iberian Margin region also shows Greenland-like structure, but with more pronounced surface cooling between interstadials and Heinrich stadials (ca. 6-9 ??C) than between interstadials and non-Heinrich stadials (ca. 2-3 ??C). The southern Nordic Seas show smaller D-O temperature anomalies (ca. 1-2 ??C) that appear out of phase with Greenland. These spatial patterns are replicated in a new global climate model simulation that features unforced (D-O-like) and freshwater forced (H-like) abrupt climate changes. The model simulations and observations suggest consistently that the spatial expression and amplitude of D-O and H event temperature anomalies are dominated by coupled changes in the Atlantic Meridional Overturning, sea ice extent, polar front position and thermocline structure. ?? 2022 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).